Eight new species of Dolichopodinae (Diptera: Dolichopodidae) from northern Iran - Kazerani, Farzaneh; Khaghaninia, Samad; Talebi, Ali Asghar; Persson, Magnus; Pollet, Marc (Zootaxa, 2017)
Dipterological surveys were conducted in different sites in western and central parts of northern Iran (Guilan, Mazandaran, Kordestan, East and West Azerbaijan and Ardabil provinces) during 2010–2011 using Malaise traps, and during 2012–2014 employing sweep nets. A total of 110 species were collected, including 42 Dolichopodinae. Eleven dolichopodine species proved new to science, eight of which are described here: Dolichopus fuscicercus sp. nov., D. subimmaculatus sp. nov., Gymnopternus flavitibia sp. nov., G. atratus sp. nov., Hercostomus setitibia sp. nov., H. albicoxa sp. nov., Poecilobothrus annulitarsis sp. nov. and P. innotabilis sp. nov. Some of these species strongly resemble European species and even share near identical conspicuous male secondary sexual characters.